2012
DOI: 10.1890/11-1803.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sampling completeness on the structure of plant–pollinator networks

Abstract: Plant-animal interaction networks provide important information on community organization. One of the most critical assumptions of network analysis is that the observed interaction patterns constitute an adequate sample of the set of interactions present in plant-animal communities. In spite of its importance, few studies have evaluated this assumption, and in consequence, there is no consensus on the sensitivity of network metrics to sampling methodological shortcomings. In this study we examined how variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(151 citation statements)
references
References 50 publications
8
139
2
2
Order By: Relevance
“…Asymptotic values of NODF were achieved earlier (day 8) than for Weighted NODF (day 16), but overall our results coincide with those of Rivera-Hutinel et al (2012) who found NODF to be relatively stable if at least 30% of the network had been sampled. However, the observed network was not significantly nested (Fig.…”
Section: Network Propertiessupporting
confidence: 88%
See 3 more Smart Citations
“…Asymptotic values of NODF were achieved earlier (day 8) than for Weighted NODF (day 16), but overall our results coincide with those of Rivera-Hutinel et al (2012) who found NODF to be relatively stable if at least 30% of the network had been sampled. However, the observed network was not significantly nested (Fig.…”
Section: Network Propertiessupporting
confidence: 88%
“…Additionally, these descriptors showed similar trends in all of our study sites, suggesting that such robustness to sample size is not network-specific but also that these descriptors are of limited informative value to compare seed dispersal networks. Previous studies on pollination networks found a tendency for an initial increase in Connectance towards an asymptote that might be reached at relatively low (Nielsen and Bascompte 2007) or higher (Rivera-Hutinel et al 2012) levels of sampling completeness. Our results suggest that, despite both Connectance and Weighted Connectance of seed dispersal networks may be stable even with a low sampling effort, they are of limited use if we want to compare at least similar seed dispersal networks.…”
Section: Network Propertiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Visitation rate was estimated by recording the number of pollinator visits to all fl owers within patches during 15 minutes focal censuses (see also Murúa et al 2010, Rivera-Hutinel et al 2012. We performed a total of 190 censuses (47.5 h of observation) in the native habitat and 108 censuses (27 h of observation) in the Pinus plantation All samplings were performed between 0900 and 1700 hours, always in sunny days.…”
Section: Methodsmentioning
confidence: 99%